PENGARUH KEMAMPUAN KERJA DAN KETERLIBATAN KERJA TERHADAP KINERJA PEGAWAI - Ld Abdul Manan; La Ode Kalimin; Wahuniati Hamid (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2019)
This study aims to: 1) find out and analyze the effect of competence and work engagement simultaneously on employees performance in the implementation of the social welfare problem management program (PMKS) at Wakatobi regency social service, 2) find and analyzing the effect of work competence on employees performance, 3) finding and analyzing the effect of work competence on employees performance. The analytical tool used is multiple regression. The result of the analysis showe that: 1) work competence and work engagement simultaneously have positive and significant effects on employees performance the implementation of the social welfare pro blem management program  (PMKS) at Wakatobi regencysocial service, 2) work competence has positive and significant effects on employees performance, and 3) work engagement has negative and significant effecs on employees performance.Keywords: work competence, work engagement, employees performance